Coherent structure of paired vortex and transition in flow pattern in cavitating jet through a poppet valve. (March 2019) - Yuan, Cong; Song, Jinchun; Liu, Minghe
Highlights: Illustrates gradual development of cavitation from inception to bubble cluster. Exhibits organization and formation of coherent structure. Captures three distinct vortex pairing processes. Discusses correlation between coherent structure and flow pattern. Reveals piecewise feature of flow performance. Abstract: A combined experimental and numerical method is performed in order to investigate the flow pattern for cavitating jet through a poppet valve. Results show that coherent structure, which is organized as paired vortex structure, is widely involved in internal dynamics of the investigated jet flow. Its formation is governed by a similar mechanism, whereas its subsequent evolution shows variation close correlated to flow pattern. Generally, transition of coherent structure leads to noticeable alteration in flow pattern. In the present case, however, it is the subsequent evolution of coherent structure that plays a determinant role for flow pattern. For low pressure drop below 25 bar in poppet valve of 0.7 mm openness, coherent structure experiences a gradual collapse, and the laminar potential core is persistent along poppet surface. For moderate pressure drop, coherent structure undergoes a progressive intensification, and the laminar flow becomes partly disturbed as a waving pattern in the wake or a further periodic cavitating pattern. With pressure drop over 36 bar, vortex evolves fast into a cavitating bubble cluster, which involves strong interaction between coherent structures. Consequently, potential core experiences a sudden and aggressive fragmentation. In addition, three kinds of vortex pairing process are captured, which are demonstrated highly involved in evolution of coherent structure and at the same time exhibit some distinctive features from conventional paring process. Furthermore, the transition in flow pattern reveals and explains the piecewise flow-rate performance. Graphical abstract: Image, graphical abstract